THE ROLE OF LEARNING FOREIGN LANGUAGES IN THE LIVE OF YOUNG PEOPLE. - Ergashxo'jayeva Shahzoda; Sayfullayeva Ruxshona; Xudoyqulova Xusnora (Scientific Impulse, 2024)
The article explains how important it is to learn foreign languages, and some tips are given for young people to make the most of such opportunities.Methods of teaching and getting young people interested in foreign languages.